2019
DOI: 10.3389/fpsyg.2019.00555
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexia Nervosa: Disorder or Not? Opinions of Dutch Health Professionals

Abstract: Introduction: Orthorexia nervosa (ON) is a condition that is characterized by a pathological obsession with eating foods one considers healthy and has recently been suggested as a new possible diagnosis. However, there is limited published research on health professionals’ recognition, ideas and opinions regarding the diagnosis and classification of ON.Purpose: The aim of this mixed-methods study was to gain insight into the perspectives of clinically active health professionals on ON, and into their opinions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
2
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 15 publications
5
36
2
6
Order By: Relevance
“…In the above case, two mechanisms would contribute to the development of ON: food restriction (from the ED spectrum) and the symptoms of OCD. This relationship was also confirmed by other studies and specialist opinions linking ON behaviours with ED and OCD (Arusoğlu et al, 2008;Asil and Sürücüoğlu, 2015;Bundros et al, 2016;Hayes et al, 2017;Poyraz et al, 2015;Ryman et al, 2019). At the same time, it is worth considering investigating the causal relationship between these classes of disorders as well as to determine the relationship between orthorexic behaviours and obsessive-compulsive personality traits, which are common in individuals with AN (Crane et al, 2007).…”
Section: Wnioskisupporting
confidence: 69%
See 1 more Smart Citation
“…In the above case, two mechanisms would contribute to the development of ON: food restriction (from the ED spectrum) and the symptoms of OCD. This relationship was also confirmed by other studies and specialist opinions linking ON behaviours with ED and OCD (Arusoğlu et al, 2008;Asil and Sürücüoğlu, 2015;Bundros et al, 2016;Hayes et al, 2017;Poyraz et al, 2015;Ryman et al, 2019). At the same time, it is worth considering investigating the causal relationship between these classes of disorders as well as to determine the relationship between orthorexic behaviours and obsessive-compulsive personality traits, which are common in individuals with AN (Crane et al, 2007).…”
Section: Wnioskisupporting
confidence: 69%
“…Choć zważanie na aspekty zdrowotne podczas dokonywania wyborów żywieniowych przez grupę HON i brak związku nasilenia cech ON z BMI są argumentami za różnicowaniem omawianego zaburzenia od AN, zasadne wydaje się zakwestionowanie odrębności psychopatologicznej ON i uznanie miejsca ortoreksji w spektrum ED. Stanowisko to podzielają inni badacze (Barthels, 2013, za: Cena et al, 2019Barthels et al, 2015;Dell'Osso et al, 2016;Łucka et al, 2019;Pietrowsky i Barthels, 2016 (Arusoğlu et al, 2008;Asil i Sürücüoğlu, 2015;Bundros et al, 2016;Hayes et al, 2017;Poyraz et al, 2015;Ryman et al, 2019). Jednocześnie warto rozważyć zbadanie zależności przyczynowo-skutkowych między wymienionymi klasami zaburzeń i określenie związku między cechami ortoreksji a obsesyjno-kompulsyjnymi cechami osobowości, częstymi u osób z AN (Crane et al, 2007).…”
Section: Discussionunclassified
“…At present, ON is a growing topic of interest predominantly in the global north with the vast majority of research focused on English-speaking populations [15,[21][22][23][24]. This represents a research gap in our understanding of the intercultural differences in the way ON manifests, is experienced, and understood.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, approximately two thirds of Dutch-speaking eating disorder professionals surveyed (n = 111), reported that they had seen ON cases in their work and thought that ON warranted more attention both clinically and in research [18]. In a more recent study, 95.6% of eating disorder specialists surveyed in the Netherlands (n = 160) stated that ON was prevalent to some extent in the general population, with the majority reporting that ON should be categorised under the Eating and Feeding Disorders category in the DSM-5 [19] 2 . At present, ON would perhaps be diagnosed as a subtype of AN, due to overlapping features between ON and AN, such as perfectionism, guilt over food transgression, trait anxiety, cognitive rigidity [20].…”
Section: Diagnosismentioning
confidence: 99%